Serum leptin, body fat, and nutritional markers during the six months post-kidney transplantation - El Haggan, Wael; Chauveau, Philippe; Barthe, Nicole; Merville, Pierre; Potaux, Luc; Aparicio, Michel (Metabolism, clinical and experimental, 2004)
Leptin is a 16-kd protein that is thought to be a regulator of food intake and body weight. Many previous studies have reported elevated serum leptin levels in renal failure. In this study, we investigated the outcome of serum leptin and its relationship to body fat (BF), dietary intake, nutritional, and inflammatory markers after kidney transplantation (KTx). A total of 41 kidney transplant recipients were followed-up prospectively during 6 months posttransplantation. Serum leptin, albumin, transferrin, and C-reactive protein (CRP) were measured at KTx, 15 days, 3, and 6 months later. Dietary intake and BF were determined at KTx, 3, and 6 months later. A decrease in serum leptin was observed early at day 15 after KTx; this decrease was significant only in patients with BF ≥ 30% of body weight. The decrease was maintained at 3 and 6 months after KTx. In multivariate analysis, an independent impact of higher percentage BF at KTx on the decrease of serum leptin was observed. Serum leptin correlated positively with BF. Conversely, no correlation was found between changes of serum leptin and changes of dietary intake. Leptin correlated positively with CRP at KTx, but not after normalization of renal function. Changes of serum leptin levels were not correlated with those of serum albumin levels. In summary, hyperleptinemia at KTx is manifest in patients with a high percentage of BF. An early and maintained correction follows KTx. Serum leptin levels did not appear to affect alimentary intake at and after KTx.